2016
DOI: 10.1186/s12950-016-0138-z
|View full text |Cite
|
Sign up to set email alerts
|

Circulating adipokine levels and prognostic value in septic patients

Abstract: BackgroundAdipokines have a wide range of effects and are linked to sepsis and septic shock. The aim of the present study was to describe the changes in adipokine levels in septic patients in relation to patients’ preseptic adipokine levels. Furthermore, we examined adipokines as prognostic markers.MethodsFourteen consecutive critically ill patients meeting the clinical criteria for severe sepsis or septic shock 3 days up to 1 month after major visceral surgery were enrolled prospectively. Plasma adipokines we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
1
11

Year Published

2017
2017
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 24 publications
1
22
1
11
Order By: Relevance
“…In sepsis, higher adiponectin levels before sepsis and decreasing adiponectin levels after sepsis are associated with survival. Additionally, compared with patients who survived sepsis, O’Brien et al found lower adiponectin concentrations before sepsis in the subgroup of patients who died during the course of sepsis [ 33 ]. Finally, obesity may be treated more aggressively than other diseases, in part because it is associated with high risks of cardiovascular disease, insulin resistance, hypertension, and other comorbidities [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…In sepsis, higher adiponectin levels before sepsis and decreasing adiponectin levels after sepsis are associated with survival. Additionally, compared with patients who survived sepsis, O’Brien et al found lower adiponectin concentrations before sepsis in the subgroup of patients who died during the course of sepsis [ 33 ]. Finally, obesity may be treated more aggressively than other diseases, in part because it is associated with high risks of cardiovascular disease, insulin resistance, hypertension, and other comorbidities [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, there are conflicting results regarding these adipokines and the outcome from sepsis [ 11 – 21 ]. Although adipokines have been associated with the prognosis of sepsis, it is not clear if adipokines promotes an infectious process to become septic or are related to the outcome of the septic event [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Increased and decreased adiponectin levels have been reported in septic patients when compared with healthy controls (24)(25)(26). Moreover, in a clinical study conducted by Hillenbrandet al, adiponectin levels measured 4 days after being diagnosed with sepsis were found to be lower than the values measured on day 1 (27). The reason for the higher adiponectin levels in sepsis patients in our study may be taking the average of adiponectin levels measured on 5 consecutive days.…”
Section: Discussionmentioning
confidence: 37%